2005
DOI: 10.1515/bc.2005.028
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ-induced focal complex formation in epithelial cells is mediated by activated ERK and JNK MAP kinases and is independent of Smad4

Abstract: Advanced malignancies often exhibit increased concentrations of transforming growth factor-beta (TGF beta), which has been suggested to promote invasion and metastasis. While inhibition of epithelial cell proliferation in response to TGF beta is mainly mediated by the well-characterised Smad pathway, the molecular mechanism leading to TGF beta-induced invasiveness and metastasis are largely unknown. To elucidate these mechanisms, we compared TGF beta1 signalling in MCF-7 and the Smad4-negative MDA-MB-468 breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
46
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 43 publications
5
46
0
1
Order By: Relevance
“…These data suggest that JNK and ERK might be targets for the inhibitory effects of ALK1. Such a link between JNK, ERK, and TGFb-family members has been previously shown by several groups (Atfi et al, 1997;Reimann et al, 1997) and evidence indicates that these kinases could be regulated by TGFb family members in a Smad-independent manner (Imamichi et al, 2005;Zhang et al, 2005). In our previous work, we could demonstrate that ALK1ca-induced inhibition of endothelial cell migration was not due to a decrease in motility but rather to a defect in cell orientation that could be visualized by a decrease in the expression of the focal adhesion protein paxillin at the edge of the wound (Lamouille et al, 2002).…”
Section: Discussionsupporting
confidence: 56%
“…These data suggest that JNK and ERK might be targets for the inhibitory effects of ALK1. Such a link between JNK, ERK, and TGFb-family members has been previously shown by several groups (Atfi et al, 1997;Reimann et al, 1997) and evidence indicates that these kinases could be regulated by TGFb family members in a Smad-independent manner (Imamichi et al, 2005;Zhang et al, 2005). In our previous work, we could demonstrate that ALK1ca-induced inhibition of endothelial cell migration was not due to a decrease in motility but rather to a defect in cell orientation that could be visualized by a decrease in the expression of the focal adhesion protein paxillin at the edge of the wound (Lamouille et al, 2002).…”
Section: Discussionsupporting
confidence: 56%
“…Although important cellular effects of TGF␤ 1 are transmitted by the Smad pathway, some Smad-independent effects have been described, such as activation of RhoA, Ras and ERK, p38 MAPK or PI3-kinase (Imamichi et al, 2005;Mulder, 2000;Bhowmick et al, 2001;Bakin et al, 2002). Whereas the phosphorylation of ␤-catenin is Smad4-independent in pancreatic cancer cells, our data show that invasion of a collagen matrix depends on Smad4.…”
Section: Discussionmentioning
confidence: 99%
“…Tyrosine-phosphorylated ShcA in turn recruits the Grb2/Sos complex that activates the Ras-Raf-Mek1-ERK1/2 cascade (Lee et al, 2007). By contrast, Imamichi and co-workers showed that the TbRI inhibitor SB431542 could not fully block TGFb-induced ERK1/2 activation, suggesting that TbRI is not involved in ERK1/2 activation (Imamichi et al, 2005). However, none of these studies specifically addressed the roles of TbRII and TbRI in TGFb signaling to ERK1/2.…”
Section: Tbri Is Not Required For Tgfb Signaling To Erk1/2mentioning
confidence: 99%